Hierarchical Zeolite: Catalyst Design by NH4OH Treatment of USY Zeolite (Adv. Funct. Mater. 46/2015). (December 2015) - Van Aelst, Joost; Verboekend, Danny; Philippaerts, An; Nuttens, Nicolas; Kurttepeli, Mert; Gobechiya, Elena; Haouas, Mohamed; Sree, Sreeprasanth P.; Denayer, Joeri F. M.; Martens, Johan A.; Kirschhock, Christine E. A.; Taulelle, Francis; et al.
Abstract : Superior catalysts are formed from ultra‐stable Y zeolite are post‐synthetic treatment with NH4 OH. On page 7130, D. Verboekend, B. F. Sels, and co‐workers show that this process results in the selective creation of small mesopores by partial zeolite densification without significant material leaching, similar to digging moles creating an interconnected network of accessible mole runs.